ESSENCE OF ENERGY SAVING STRATEGY IN INDUSTRIAL ENTERPRISES - E. Yurina; Y. Kulikova; D. Pustovalov (Вестник Северо-Кавказского федерального университета)
This article examines the role of energy conservation and energy efficiency in the country’s economy as an important factor in economic growth. The relevance of the topic is due to the fact that the electric power industry and the energy-saving industry are very important areas in the national economy. It should be emphasized that a country with low energy consumption can achieve the same results as other countries, not only being economically stable, but also reducing the pollution of its territory from various energy waste. The article proposes energy saving strategies for industrial enterprises.